Determinants of Factors Affecting the Use of Maternal and Child Health Book in Early Detection of Pregnancy Risks and Child Growth - Teta Puji Rahayu; Tinuk Esti Handayani; Agung Suharto (Aloha International Journal of Health Advancement (AIJHA), 2019)
Introduction: Efforts to reduce MMR and IMR include increasing maternal knowledge. One of the government's efforts to improve maternal knowledge is by making a maternal and child health book that can be used as a practical guide to address various health problems, including maternal and child health. The purpose of this study was to analyze the relationship of maternal factors such as age, education, occupation, parity, knowledge, maternal attitudes, ownership of health insurance and family support that affect the use of maternal and child health book (MCH book). Methods: This type of research was cross sectional study, using a questionnaire. The research sample was 170 mothers who had toddlers in Magetan district, using cluster random sampling technique for the sub-district, while for the village, posyandu, and respondents were taken by simple random sampling. Data analysis using Chi square and multiple logistic regression. Result: There was no significant effect between age, education, occupation, parity, ownership of health insurance, maternal attitudes and family support for the behavior of the use of maternal and child health books. Knowledge had a significant effect on the behavior of using maternal and MCH book (p-value = 0.011). Conclusion: Knowledge plays a role in the behavior of using MCH book so that they can contribute to the reduction of maternal and infant mortality. It is necessary to examine further other factors that contribute to the use of MCH book such as maternal motivation, support from health workers, the influence of government policies, and the influence of cadre support with different research designs. Keywords: Age, Education, Employment, Parity, Knowledge, Attitude, Health insurance, Family support